Oral and maxillofacial dental care professionals in critical care during the COVID-19 pandemic. Issue 1 (January 2021) - Forrester, S.; Fisher, G.; Chieng, C.Y.; Rogers, S.N.
Abstract: At the peak of the COVID-19 pandemic there was a 'call to arms' across the oral and maxillofacial staff. This article reports on the extended role of the department's dental care professionals (DCPs) and the tremendous opportunity and value that temporary redeployment presented.